ANALISIS TAX BUOYANCY DI INDONESIA - Sarah Nur Balqis; Miksalmina Miksalmina (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
Abstract The purpose of this study is to analyze the response of tax revenues changing due to economic conditions changing based on gross domestic product in Indonesia. This is called tax buoyancy. The variables that used in this study are total tax revenue and gross domestic product during the period 1990 - 2020. The source of data from the Central Statistics Agency and the Ministry of Finance. The model used is the double log regression model. The result of the analysis is the response is elastic which is 1.72. This means that the changing of tax revenues is higher than changing in gross domestic product. Therefore, Indonesian government should maintain the economic growth in order to maintain the total tax revenue economic greater than gross domestic product sustainably.Keywords: Tax Revenue, Gross Domestic Product (GDP), Tax buoyancy, Indonesia